1992
DOI: 10.2105/ajph.82.10.1361
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy among the Hmong: birthweight, age, and parity.

Abstract: OBJECTIVES. The influx of Southeast Asians into the United States allows for the study of this special population and contributes to a broader understanding of reproductive health. METHODS. We used information on birth certificates to identify 1937 Hmong children born 1985 through 1988 in California, and we compared birthweight and reproductive factors as related to these children with the same factors as related to 3776 White, non-Hispanic children born in the same period. RESULTS. Mean birthweight among Hmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Despite significant heterogeneity, migrant women from Vietnam, Thailand, Cambodia, and Laos had lower risks of caesarean compared to non-migrant women in all nine included studies [15,16,37,46,48,49,51,60,61]. Focusing on Vietnamese women, two older studies found Vietnamese to have caesarean rates lower than Australian-born [OR= 0.87 (95% CI=0.75, 1.00] [49,60].…”
Section: Resultsmentioning
confidence: 99%
“…Despite significant heterogeneity, migrant women from Vietnam, Thailand, Cambodia, and Laos had lower risks of caesarean compared to non-migrant women in all nine included studies [15,16,37,46,48,49,51,60,61]. Focusing on Vietnamese women, two older studies found Vietnamese to have caesarean rates lower than Australian-born [OR= 0.87 (95% CI=0.75, 1.00] [49,60].…”
Section: Resultsmentioning
confidence: 99%
“…Eligibility was restricted to married couples in which the woman was between the ages of 18 and 46 at FRIENDS enrollment and the husband was at least 18 years of age. Because Hmong women have been reported to continue childbearing at later ages (Helsel, et al, 1992), the baseline enrollment criterion for women was extended beyond the traditional upper limit of age 40 commonly used in studies of reproductive outcomes. Through November 2005, a total of 175 enrolled couples completed baseline questionnaires which collected information on demographic and lifestyle factors, fish consumption patterns, exposure histories, and reproductive history at enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…Some are socio-economic while others are behavioral and personal in nature. Among the socio-economic and demographic factors affecting birth weight are maternal age (such that women under 20 and over 35 are at a higher risk of delivering a low birth weight infant), labor force status (working mothers tend to experience greater risks [Peoples-Sheps, Siegel, and Suchindran 1991], particularly in occupations that expose women to second-hand smoke [Bakketeig et al 1993]), education level (higher education leads to lower rates of low birth weight [Duncan and Laren 1990]), parity (first borns are more often of low birth weight [Helsel, Petitti, and Kunstadter 1992]), birth spacing (pregnancies spaced close together are more likely to result in low birth weight [Klebanoff 1988]), maternal stature, weight before pregnancy, and weight gain during pregnancy. Behavioral factors such as alcohol or drug use by the mother have long been known to increase the risk of low birth weight (Cornelius et al 1995).…”
Section: Social Determinants Of Birth Weightmentioning
confidence: 99%